Self-presentation strategies in online dating of couples with successful relationships - Francisco, Winnie B. (Animo Repository, 2017)
Online dating is becoming more common as a medium in finding relationships, although deception is highly likely in this field as suggested by recent researches. In online dating environments, participants have greater control over their self-presentational behavior and are able to strategically manage their online interactions. This research studies the self-presentation strategies of online daters and how they manage challenges that occur while online dating, and also the factors that contribute to the development of a successful relationship. Responses from the participants showed a small-scale of difference in variation. Through the analysis of data gathered, the researchers were grouped together common themes that emerged. Physical appearance, deception, and a feeling of love towards each other were the prominent ones that occurred. These themes gathered made sense of the phenomenon. Participants relied heavily on physical appearance by choosing profile photos that showcased their best physical attributes that were used to attract the opposite gender. This strategy is ranked highest as the facet that online dating users discern upon checking the application or website. However, unfortunately, due to the anonymity, the abundance of fake identities and individuals who portray a facade is deemed to be the biggest challenge for online dating. On the other hand, what contributes to the relationship longevity is the feeling of love towards each other, wherein a foundation is gradually built on trust and understanding from both partners, as well as spending time with each other and having mutual understanding or empathy.